Achieving stable actuation response and elastocaloric effect in a nanocrystalline Ti50Ni40Cu10 alloy. (15th March 2023) - Dang, Pengfei; Zhou, Yumei; Pang, Jianbo; Ding, Xiangdong; Sun, Jun; Lookman, Turab; Xue, Dezhen
Abstract: Shape memory alloys with good functional fatigue property are in demand in practical applications such as solid-state actuators and eco-friendly refrigerators. In the present study, the functional stability of Nitinol (Ti-Ni alloy) was improved by combining Cu-doping and nanocrystallization. The target alloy maintains almost constant transformation temperatures in both stress-free and load-biased thermal cycles, showing a stable thermal actuation response. Moreover, a large adiabatic temperature change of over 20 K is obtained without much degradation in the course of 200 tensile cycles. The detailed microstructural observation reveals that the excellent functional stability in the alloy originates from both the improvement of lattice compatibility brought about by doping and the strengthening effect provided by the nanocrystalline structure. Graphical abstract: